STUDI PENINGKATAN KESIAPAN GURU SEKOLAH DASAR DALAM PENYUSUNAN RPP IMPLEMENTASI KURIKULUM 2013 - I Ketut Ngurah Ardiawan (Widyacarya: Jurnal Pendidikan, Agama dan Budaya, 2018)
This study consists of compilation of information from the literatures and researcheson teacher preparedness in creating lesson plan which implement Curriculum 2013. This methodis called "Meta-Analysis". The analysis used in this study are series of quantitative analyticaltechniques that allow the synthesis of various researches in one topic. Based on the findingsabove, some alternative policies can be given as follows: providing opportunities and supportfor teacher to continue to higher education, supervising both class and administrative work,optimizing teachers’ participation in workshop for the implementation of curriculum 2013,utilizing integrated thematic technology-based learning media, conducting action researcheson learning activities for Curriculum 2013, conducting problem solving and self evaluation forthe learning process in Curriculum 2013 and conducting comparative studies to other schoolsthat have become pilot projects of Curriculum 2013 especially qualified schools that are able toimplement this curriculum both in classroom and out-of-class learning processes. Thus, theteachers’ preparedness in designing the lesson plans based on Curriculum 2013 can be completedin accordance with the plan, guidelines and demands in standard of process.